The messy lives of book people eaudiobook - Patrick, Phaedra (2022)
The house cleaner of a famous author must carry out her employer's shocking last wish in this delightful new novel from beloved author Phaedra Patrick Mother of two Liv Green barely scrapes by as a maid to make ends meet, often finding escape in a good book while daydreaming of becoming a writer herself. So she can't believe her luck when she lands a job housekeeping for her personal hero, megabestselling author Essie Starling, a mysterious and intimidating recluse. The last thing Liv expected was to be the only person Essie talks to, which leads to a tenuous friendship. When Essie passes away suddenly, Liv is astonished to learn that her dying wish was for Liv to complete her final novel. But to do so Liv will have to step into Essie's shoes. As Liv begins to write, she uncovers secrets from the past that reveal a surprising connection between the two women—one that will change Liv's own story forever... Don't miss Phaedra Patrick's uplifting new novel, The Little Italian Hotel! Check out these other heartwarming stories from Phaedra Patrick: The Curious Charms of Arthur Pepper Rise and Shine, Benedict Stone The Library of Lost and Found The Secrets of Love Story Bridge